Tinjauan Yuridis Terhadap Pasal 217 dan 240 Undang-Undang Nomor 1 Tahun 2023 Tentang KUHP - Ahmad Fatih Karomi; Rizky Ahadyan Ardyansyah (MLJ Merdeka Law Journal, 2025)
This research examines the implementation of Law No. 1 of 2023 concerning the Indone- sian Penal Code, specifically Articles 217 and 240, which effectively restrict citizens' rights to express their opinions. Cases such as those involving Ahmad Dhani and Haris Azhar-Fatia highlight how legal provisions intended for protection are instead used to silence dissenting voices. The Constitutional Court had previ- ously clarified in Decision No. 013-022/PUU-IV/2006 that these restrictions on freedom of expression are inconsistent with the constitution. However, the reality on the ground shows that this ruling is not being enforced. This study employs a qualitative approach to thoroughly analyze legal provisions related to defamation of the President and state institutions. The analysis reveals that Articles 217 and 240 of the Penal Code conflicts with human rights principles, particularly freedom of expression. The broad interpretation of these articles poses a significant threat to democracy. The urgency to revise these articles in alignment with democratic values is increasingly evident.